Prerequisites for Effective Motivation of Employees (Economic journal of Lesya Ukrainka Volyn National University, 2017)
It is very important to motivate employees in the process of their work to achieve high productivity. For betterunderstanding of the meaning of motivation, the article investigates the essence and the meaning of human labor. It is provedthat the most valuable is the work, where the employee feels their own necessity and usefulness. This opinion is more closelyadhered to by employees of the mature age. Those kinds of work where organization of work is better, teamwork ispreferable, working conditions arefavorable become more attractive to youngemployees. Middle ageworkers are interestedtoincrease their vocational qualifications, whereas achieving a certain age limit, this pattern begins to decline. The importantfactors in the staff motivation are the subjective factors of the choice of profession and the level of skills, determined by thelevel of prestige of work. Certain groups of factors influence the quality of the work and jobsatisfaction. However, the articlenotes that there are more factors that decrease the level of readiness to work. The reasons to demotivate the staff are asfollowing: unfair payment, poor working conditions, lack of organizational clarity, inappropriate leadership style, badlyformed corporate culture, lack of professional growth, lack of training opportunities, lack of qualified professionals andmanagers who are able to evaluate and decide whether the candidate is skilled enough to suit the available vacancy, inabilityto provide high-skilled workers with their further growth, recruitment of employees who are not interested in the job,discrepancy between expectations of employees and the enterprise, the inability of the employee to respond quickly andmake the right decisions in a non-standard situation, the absence of conditions under which the employee’s motives wouldcontribute to his effective professional activities, etc.Understanding of the reasons for reducing of motivation is the key to successful personnel management.
Keywords: systems of labor motivation, work content, demotivators, directions of labor efficiency increasing.